The Training on Waste Sorting and Composter Making in Dukuh Pereng Kembang, Gamping, Sleman - Wijhati, Ellyda; Kristianingsih, Riska; Rahmawati, Angger Ayu Nur; Prasetyo, Raditya Rahardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Waste management remains a significant challenge due to inefficient waste disposal methods, including in Dukuh Perengkembang, Balecatur Village, Sleman, Yogyakarta, where the accumulation of organic waste has become an urgent issue following the closure of the Piyungan Integrated Waste Disposal Site in Yogyakarta. The lack of awareness and improper waste sorting hinder its effectiveness. To address this, students from Community Service Program (CSP) Group 50 took the initiative to provide composting training to convert organic waste into compost, which not only reduces the burden on landfills. The implementation method includes counseling on making composters, practical sessions on creating composters, and monitoring and evaluation of their use. The training participants are housewives in the Dukuh Perengkembang area. As a result of the training, there was an increase in knowledge about waste sorting, and participants were able to use the composters they made to reduce the volume of waste disposed of at the waste disposal site